1998
DOI: 10.1177/002215549804600910
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Gross Cystic Disease Fluid Protein-15/Prolactininducible Protein in Rat Salivary Glands

Abstract: Gross cystic disease fluid protein-15 (GCDFP-15)/prolactin-inducible protein (PIP) is present at moderate levels in human submandibular and sublingual glands and is barely detectable in human parotid gland. The rodent homologue, PIP, has previously been identified in adult submandibular and lacrimal glands. Here we present the molecular characterization of rat PIP and show that this protein is a product of neonatal and adult rat submandibular, sublingual, and parotid glands. cDNA clones encoding rat PIP were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
40
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 44 publications
2
40
0
Order By: Relevance
“…It is also known as gross cystic disease fluid protein-15 (GCDFP-15), which associates with secretory cell differentiation and is believed to originate from a limited set of tissues, including breast and salivary glands. PIP/GCDFP-15 has been reported to be expressed in rat salivary glands (Mirels et al, 1998). Expression of GCDFP-15/PIP homologue was also reported in mouse salivary gland, although its function is still doubtful (Lamy et al, 2010;Lamy and Mau, 2012), and the expression PIP homologue was also reported in Bos taurus cattle (Zimin et al, 2009).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…It is also known as gross cystic disease fluid protein-15 (GCDFP-15), which associates with secretory cell differentiation and is believed to originate from a limited set of tissues, including breast and salivary glands. PIP/GCDFP-15 has been reported to be expressed in rat salivary glands (Mirels et al, 1998). Expression of GCDFP-15/PIP homologue was also reported in mouse salivary gland, although its function is still doubtful (Lamy et al, 2010;Lamy and Mau, 2012), and the expression PIP homologue was also reported in Bos taurus cattle (Zimin et al, 2009).…”
Section: Resultsmentioning
confidence: 98%
“…The PIP is a prolactin and androgen regulated product of human breast tumor cell line T-47D (Mirels et al, 1998). It is also known as gross cystic disease fluid protein-15 (GCDFP-15), which associates with secretory cell differentiation and is believed to originate from a limited set of tissues, including breast and salivary glands.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining known sublingual secretory proteins are products of the serous demilunes. All known serous demilune-specific proteins-SMGB, PSP, and CSP-1 (as well as prolactin-inducible protein (PIP) (Mirels et al, 1998a) and peroxidase (Moriguchi et al, 1995;Redman et al, 1998), which were not examined in the current study)-are also products of the immature acinar cells of the developing parotid and submandibular glands (Strum, 1971;Yamashina and Barka, 1972;Redman and Field, 1993;Mirels et al, 1998a).…”
mentioning
confidence: 75%
“…At early stages, type IIIP cells may contain a mixture of these heterogeneous secretory granules and typical type III cell granules containing only neonatal proteins, whereas later in development, type IIIP cells with both type IIIP and adult MGs are found. Some proteins characteristic of the neonatal submandibular proacinar cells (PIP and peroxidase) are also produced by the mature seromucous acinar cells (Strum and Karnovsky, 1970;Mirels et al, 1998a), whereas the major proacinar cell products (SMGB, SMGD, CSP-1, and PSP) are present only in some intercalated duct cells in the adult gland.…”
mentioning
confidence: 99%
See 1 more Smart Citation